2006
DOI: 10.1242/jcs.03206
|View full text |Cite
|
Sign up to set email alerts
|

Host cell Ca2+ and protein kinase C regulate innate recognition ofToxoplasma gondii

Abstract: There was an error published in J. Cell Sci. 119, 4565-4573.In Fig. 7C, the 1 mM and 5 mM bars were incorrectly labelled. The corrected figure and legend are shown below. The authors apologise for this error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 69 publications
2
17
0
Order By: Relevance
“…Because some of these pathways are also implicated in stimulating EGR-dependent transcription (31, 71), we sought to determine what role, if any, they played in Toxoplasma induction of EGR2. To specifically inhibit host cell Ca 2ϩ signaling during Toxoplasma infection, we pretreated host cells with BAPTA-AM and then extensively washed the cells before infecting them with parasites in BAPTA-AM-free medium (43). EGR2 mRNA levels measured 6 h postinfection indicated that chelating host cell intracellular calcium increased Toxoplasma-stimulated EGR2 expression with marginal statistical significance (Student's t test; P ϭ 0.058) (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Because some of these pathways are also implicated in stimulating EGR-dependent transcription (31, 71), we sought to determine what role, if any, they played in Toxoplasma induction of EGR2. To specifically inhibit host cell Ca 2ϩ signaling during Toxoplasma infection, we pretreated host cells with BAPTA-AM and then extensively washed the cells before infecting them with parasites in BAPTA-AM-free medium (43). EGR2 mRNA levels measured 6 h postinfection indicated that chelating host cell intracellular calcium increased Toxoplasma-stimulated EGR2 expression with marginal statistical significance (Student's t test; P ϭ 0.058) (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Increases in intracellular Ca 2ϩ levels as well as activation of MAPKs (p38, extracellular signalregulated kinase [ERK], and c-jun N-terminal protein kinase) and phosphoinositide-3 kinase (PtdIns-3K) are signaling events triggered in Toxoplasma-infected cells (33,34,43). Because some of these pathways are also implicated in stimulating EGR-dependent transcription (31, 71), we sought to determine what role, if any, they played in Toxoplasma induction of EGR2.…”
Section: Resultsmentioning
confidence: 99%
“…These data agree with other experimental models that demonstrated that NO is not detected in large amounts in human systems. 49 The low parasitism observed in the first-trimester explant experiments may be related to a particular role of MIF that mediates a proinflammatory profile after stimulus in the presence of immunosuppressive hormones. 39 Alternatively, in thirdtrimester placental explants, MIF controlled T. gondii infection only at the highest concentration of this cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, PKC is suggested to act as a critical regulatory kinase in the initiation of diverse innate immune responses (33). Furthermore, identification of signaling partners of the NOD2-iNOS-Notch1-PI3K axis that are critical in driving the expression of anti-inflammatory molecular signatures, assumes novel significance.…”
Section: Inos/no Axis Is An Essential Link In Nod2-driven Notch1mentioning
confidence: 99%